The Inhibiting Effect of a Plasma Globulin on Arterial Thrombus Formation (as Compared to Dipyridamole) - Bourgain, R H; Six, F; Smets, P (Thrombosis and Haemostasis, 1978)
The inhibiting effect on arterial white thrombus formation of a globulin prepared from beef plasma has been compared to dipyridamole in white Wistar rats. It was demonstrated that the globulin fraction had a greater effect in inhibiting thrombus formation as judged by the lag time [t(1)], the maximal thrombus value [m(T)], the maximal thickness of the thrombus [m(D)] and the maximal thrombus surface [m(O)].